Design Institutes & Design Studios: Cases of permeability between teaching and practice (including research) (EAAE Annual Conference Proceedings, 2023)
The aim of the contribution is describing an urban design teaching activity developed in the last eight years (2016-2023) at one of the top Schools of Architecture in China: the Design Studios “Urban morphology, architectural typology, contemporary settlement patterns” held at the School of Architecture in Southeast University Nanjing, China.